Tissue-Specific Transcriptomics Reveals an Important Role of the Unfolded Protein Response in Maintaining Fertility upon Heat Stress in Arabidopsis. Issue 5 (24th April 2017) - Zhang, Shuang-Shuang; Yang, Hongxing; Ding, Lan; Song, Ze-Ting; Ma, Hong; Chang, Fang; Liu, Jian-Xiang
Abstract : This work reveals both the tissue-specific heat responsiveness of Arabidopsis at the reproductive stage and downstream genes of the UPR regulators important in maintaining fertility upon heat stress. Abstract: High temperatures have a great impact on plant reproductive development and subsequent fruit and seed set, but the underlying molecular mechanisms are not well understood. We used transcriptome profiling to investigate the effect of heat stress on reproductive development of Arabidopsis thaliana plants and observed distinct response patterns in vegetative versus reproductive tissues. Exposure to heat stress affected reproductive developmental programs, including early phases of anther/ovule development and meiosis. Also, genes participating in the unfolded protein response (UPR ) were enriched in the reproductive tissue-specific genes that were upregulated by heat. Moreover, we found that the UPR -deficient bzip28 bzip60 double mutant was sensitive to heat stresses and had reduced silique length and fertility. Comparison of heat-responsive wild type versus bzip28 bzip60 plants identified 521 genes that were regulated by bZIP28 and bZIP60 upon heat stress during reproductive stages, most of which were noncanonical UPR genes. Chromatin immunoprecipitation coupled with high-throughput sequencing analyses revealed 133 likely direct targets of bZIP28 in Arabidopsis seedlings subjected to heat stress, including 27 genes that were also upregulated by heat during reproductive development. Our results provide important insights into heat responsiveness in Arabidopsis reproductive tissues and demonstrate the protective roles of the UPR for maintaining fertility upon heat stress.